Classical forms of investment of awqaf: a juristic analysis - Osmani, Noor Mohammad; Rahman, Md. Habibur (2015)
There is no denying that throughout the ages awqaf (endowments) had a great contribution to make a comprehensive development of, not only Islamic, but also human civilization. Thus, taking an attempt to revitalize the role of awqaf is actually trying to bring back a gigantic voluntary institutional role to serve for the advancement of society and civilization. Hence, this paper intends to make a juristic study on utilizing awqaf funds through investment and financing, extending from the classical modes to the contemporary modes thereof. The paper will be qualitative in nature, in which analytical and descriptive methods would be followed. The analysis will be relying on respective classical and contemporary juristic views and discussion. The paper posits that, investment of awqaf properties is basically in two types, investment of the original awqaf assets and investment of the proceeds yield from the original awqaf assets. The investment modes which will be discussed in the paper along with respective juristic issues and discussion are, for example, hikr (long lease with large advance lump sum), lease with dual payment, kadik (tenant's improvements to rental property), mursad (construction for rent swap with a waqf), sharecropping, partnership, diminishing partnership, manufacturing arrangement, lease ended with ownership as well as investment in purchasing permissible financial papers and securities. Last but not least, the paper elucidates the issue of substitution and modification of awqaf properties as it carries more significance in terms of the economic aspects of awqaf.